OPTIMALISASI PENGENALAN DAN EDUKASI PERBANKAN SYARIAH MELALUI PROGRAM PEMBUKAAN REKENING MASSAL DI KANTOR KPU KABUPATEN BANTEN - Hanrieka, Yasmin Nabila; Haura, Arie (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2024)
This research is one of the teacher's efforts to increase students' interest in learning by using various kinds of learning media. Audio-visual is one of the media used, but the problem in this research is how audio-visual media influences Madrasah Ibtidaiyah students' interest in learning. This research aims to determine the effect of audio-visual learning media on students' interest in learning at MIS Darul Ihya. This research uses quantitative methods using data collection techniques through questionnaires, documentation, and observation assisted by Mrs. Excel. The subjects of this research were class IV students at MIS Darul Ihya. The research results show that students are thrilled, enthusiastic, and very interested in using audio-visual learning media during the teaching and learning process. With very high student interest and interest, student learning outcomes will be influenced.